Motion analysis-based application for enhancing physical education - Hasan, Kahtan; Suryanti, Awang; Tuty Asmawaty, Abdul Kadir; Maath S., Abdulghafoor; Tuan Siti Shahirah, Tuan Shamsuri (American Scientific Publisher, 2018)
Physical education plays an important role in positively influencing students to develop a good learning process and a healthy lifestyle. Moreover, physical education assists students and athletes in developing muscular strength, maintaining fitness, and improving cardiovascular health. Issues arise when the lack of actual pattern of movement of children in sports leads to difficulties in implementing the correct movement, thereby decreasing the interest of students in physical education and students may suffer from muscular injury if they make the wrong movement. In this study, a human motion analysis method is utilized to overcome the abovementioned issues. Human motion analysis supports physical education in analyzing human movement behavior or patterns in conducting physical activities. Thus, this paper aims to develop an application for teaching students to perform the correct movement during physical education courses using motion analysis, which can help reduce the threats to physical education and solve its main issue, which is injury in athletes. The proposed application is expected to increase the interest and participation levels of students in physical education courses.